The effect of exercises (weights, rubber ropes) on the development of physical abilities, movement and improvement of achievement in swimming (50) m freestyle for youth - JASSIM Al-YASIRI, MUHAMMAD; MUHI KHALEEL Al-QAZWINI, AMMAR (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed to prepare exercises (weights, rubber ropes) in developing the physical and mobility abilities of young swimmers and improving their achievement in swimming 50 meters freestyle. To achieve this aim, the researchers use the experimental procedure (equipotent groups) to fit the problem, and the research identifies the youth swimmers for 50 m freestyle in the clubs of Najaf who are 8 swimmers. For the purposes of the research experiment, (6) swimmers were randomly selected, and (3) swimmers were selected for each of the first experimental research groups (weights) and the second experimental group (rubber ropes). Each swimmer has 7 attempts, and there are a total of 21 attempts for each group, and after completing the test process for the research variables, which is extracting the results and treating them statistically, the researchers reached some conclusions, including:1. Both weight training and rubber ropes positively affected the development of physical and movement abilities and achievement in the 50 m freestyle swimming for young swimmers.2- Weight training came with the best influence in developing the explosive ability of the two legs and the least improvement in the rubber rope exercises.3- The rubber rope exercises showed a preference in impact to develop (the strength distinguished by the speed of the two legs and the distinctive strength of the speed of the arms and agility) and to improve the achievement of youth in swimming (50) meters freestyle compared to their achievement with weight training.